SOIL MICROBIAL POPULATION AND SOIL ENZYME ACTIVITY ON PT BUKIT ASAM VARIOUS RECLAIMED LAND SITES IN SOUTH SUMATRA - Hengki Tornando; Firdaus Alam Hudi; Lilik Budi Prasetyo; Dwi Andreas Santosa (SEAMEO BIOTROP, 2018)
Open mining activities result in decreased microbial biomass and negatively impact soil fertility. Soil microbes play a key role in the decomposition of soil organic matter and in nutrient cycling through mineralization mediated by the enzymes they produce. The purpose of this study was to analyze soil fertility levels at PT Bukit Asam’s various reclaimed land sites in Muara Enim Regency, South Sumatra, Indonesia, as determined by microbial populations and soil enzyme activity. The research was conducted using an explorative method across PT Bukit Asam’s reclaimed land sites. Soil samples from seven reclamation areas of different ages were analyzed. Our results showed that soil conditions and enzyme activity vary with reclamation age. At KTU, a 12-year-old reclaimed site, urease enzyme activity was 68.83 mg NH₄⁺·g⁻¹ dm·h⁻¹, with a microbial population of 82.64 × 10⁴ CFU·g⁻¹ soil. The highest phosphatase activity, 95.66 mg pNP·g⁻¹ dm·h⁻¹, was observed at the 9-year-old SP702 reclaimed site, with a soil pH of 5.23. Cellulase activity at the 21-year-old Udongan site was 21.51 mg GE·g⁻¹ dm·h⁻¹, with a cellulolytic microbial population of 1.9 × 10⁴ CFU·g⁻¹ soil, higher than at other reclamation sites. Invertase activity at the 15-year-old Tupak site was 24.37 mg GE·g⁻¹ dm·h⁻¹. Soil enzyme activity can serve as an indicator of soil quality and microbial activity, reflecting biochemical transformations in the soil and exhibiting high sensitivity to environmental changes.